Analysis of the four basic language skills within the framework of 21st century skills - Cinkara, Emrah; Doğan, Yunus; Tiryaki, Esra; Batdi, Veli (Nova Science Publishers, Inc., 2024)
The evolution of educational philosophies in the 21st century has necessitated significant changes in educational programs worldwide. With technological advancements and the globalization of societies, education systems have adapted to meet evolving needs. The Turkish education program has also undergone renewal to align with these changes, adopting an innovative perspective. Central to Turkish education is the development of listening, speaking, reading, and writing skills, which are considered fundamental in the 21st century. A comprehensive study analyzed 45 articles and theses along with various educational resources to understand the landscape of language skill development. These studies reflect a shift away from rote learning towards fostering critical thinking and effective communication. Skill acquisition involves not only acquiring knowledge but also internalizing and applying that knowledge in practical contexts. Turkish language education focuses on cultivating critical thinking, inquiry, and research skills, recognizing that listening and reading facilitate understanding, while speaking and writing enable expression. Turkish language teachers play a crucial role in guiding students to develop these essential language skills. They must tailor teaching materials and lesson plans to engage students effectively, often incorporating literary genres such as lullabies, nursery rhymes, fairy tales, and stories to enhance reading, writing, speaking, and listening abilities. Effective language education not only impacts students' academic performance but also influences their social interactions, family relationships, and future endeavors. Language skills are foundational to communication, self-expression, and knowledge acquisition, underscoring the importance of comprehensive language education from early childhood through secondary education. The overarching goal of the Turkish curriculum is to empower students to think critically, communicate effectively, solve problems, and become lifelong learners. Achieving this goal relies heavily on skilled and dedicated teachers who foster active learning environments and guide students towards academic and personal growth. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Four language skills, 21st century skills; Language; Language teaching